Experimental work of forming professional foreign language competence of law students - Dina, Demchenko (2021)
The article is devoted to the problem of formation of professional foreign language competence of future lawyers in non- linguistic surrounding at the Yaroslavl Mudriy National Law University. With this aim pedagogical experiment was held, which included three stages: axiological, formational, monitoring. Research of the formed professional foreign language competence defined with the help of specially created tests, solution of situations and evaluation of teachers, communications with them. Probability of the results was done by the detailed organization of the experimental, representative choice of students, who participated in the experimental work, differences and similarities of methods of research, according to tests of research. The effectiveness of the system of professional training of future specialists is mostly defined by how consistently it is taken into account. Both students and professors understand the dependence of success of legal activity on the level of formed professional foreign language competence. Professional foreign language competence of future representative of legal profession, prioritize knowledge of foreign professional terminology, knowledge of   legal systems of foreign countries. In addition to knowledge, students and professors noted the importance of applying this knowledge in practical international activities to  achieve the success in formation of foreign language competence of future lawyers.